The Phenomenon of the 60ies literature: ideological preconditions and axiological landmarks (Literatures of the World: Poetics, Mentality and Spirituality, 2015)
The article studies the formation of the phenomenon of the Ukrainian sixtiers, traces the historical and particularly ideological origins and preconditions of this extraordinary occurrence, determines levels and areas of the confrontation of the sixtiers against the Soviet system. One of the central aspects of the article is to assess the repressive functions of the Ukrainian Writers’ Union as an instrument of totalitarian power concerning the persecution of the sixtiers for political reasons and the fundamental differences on the axiological level.
Keywords: sixtiers; the Writers’ Union; Khrushchev Thaw; a conflict of generations; dissent; freethinking; iterature; writer